Students' Misconceptions: Viewed from Students' Perceptions on Magnetic Field Learning - Maison Maison; Dwi Agus Kurniawan; Fauziah Yolviansyah; Rizka Octavia Sandra; Muhammad Iqbal (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Misconceptions are errors in connecting concepts that result in understanding new ideas and concepts in students' minds into wrong concepts. This study aims to analyze the effect of critical thinking skills on misconceptions in magnetic field material. The research method used in this study is mixed method. In this study, the sampling technique used was a simple random sampling technique to take the sample from the population. The sample used was 30 students taken randomly through a lottery, so 30 students were obtained as samples. The data collection instruments used in this study were interview sheets and questionnaires. The research design used was a sequential explanatory design. From the descriptive results of the misconceptions data, it is found that the mean of students' misconceptions is 3.59, which means that students' misconceptions are still relatively low. The descriptive results of critical thinking skills data show that the mean of critical thinking skills is 64.03, which means students' critical thinking skills are in a good category. The regression coefficient indicates an influence of critical thinking skills on misconceptions that can be seen from F_ = 28,740 with a significance/probability level of 0.001 < 0.05. It was concluded that there was an effect of critical thinking skills on misconceptions, seen from the higher the value of critical thinking skills, the lower students experiencing misconceptions.